2021
DOI: 10.3389/fpsyg.2021.790423
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theory of Emotions in Competitive Sports

Abstract: In this article, we introduce a theory on the dynamic development of affective processes, affect regulation, and the relationship between emotions and sport performance. The theory focusses on how affective processes emerge and develop during competitive sport involvement. Based on Scherer’s component process model, we postulate six components of emotion that interact with each other in a circular fashion: (I) triggering processes, (II) physiological reactions, (III) action tendencies, (IV) expressive behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 139 publications
1
15
0
Order By: Relevance
“…Blakemore (2019) be implemented as a new psychological approach in order to ease the regulation of different emotions during the competitions without distraction by extraneous factors. According to Jekauc et al (2021) theory, there are six ways to control emotions during sports competitions and prevent the effect. Among them: regulation of the triggering processes; usage of muscles relaxation techniques (progressive muscle relaxation); action tendencies regulation (into suitable and targeted actions); conscious choice of the way to express a desired affective state; awareness of the personal affective states; emotional regulation through the higher cognitive processes (imagination of desired states, setting and achieving goals, controlling thoughts).…”
Section: Phycological Aspect In Team Games' Activitiesmentioning
confidence: 99%
“…Blakemore (2019) be implemented as a new psychological approach in order to ease the regulation of different emotions during the competitions without distraction by extraneous factors. According to Jekauc et al (2021) theory, there are six ways to control emotions during sports competitions and prevent the effect. Among them: regulation of the triggering processes; usage of muscles relaxation techniques (progressive muscle relaxation); action tendencies regulation (into suitable and targeted actions); conscious choice of the way to express a desired affective state; awareness of the personal affective states; emotional regulation through the higher cognitive processes (imagination of desired states, setting and achieving goals, controlling thoughts).…”
Section: Phycological Aspect In Team Games' Activitiesmentioning
confidence: 99%
“…Considering that situations toward the end of a competition are typically appraised as more important (Jekauc et al, 2021), it has been shown that players' affective states were easier to recognize at later phases during a competition (e.g., Fritsch et al, 2023). This result suggests that certain situational factors and associated appraisal processes may partly explain the affective dynamics during a sports competition, which is reflected, among other things, in the intensity of players' emotional expressions (Jekauc et al, 2021). Given that emotional mimicry is an important mechanism for the transfer of emotions (Hatfield et al, 2014), emotions expressed at a higher intensity may then increase the likelihood for emotions being transferred between individuals in such situations.…”
Section: Antecedents Of Emotional Convergencementioning
confidence: 99%
“…In this regard, it can be helpful to refer to appraisal emotion theories, postulating that appraising a situation as relevant to one's goals is an important trigger for emotions (Lazarus, 1991). Considering that situations toward the end of a competition are typically appraised as more important (Jekauc et al, 2021), it has been shown that players' affective states were easier to recognize at later phases during a competition (e.g., Fritsch et al, 2023). This result suggests that certain situational factors and associated appraisal processes may partly explain the affective dynamics during a sports competition, which is reflected, among other things, in the intensity of players' emotional expressions (Jekauc et al, 2021).…”
Section: Antecedents Of Emotional Convergencementioning
confidence: 99%
See 2 more Smart Citations